Evaluation of selected wastewater treatment plants on UiTM Shah Alam Campus / Rusmini Ibrahim - Ibrahim, Rusmini (2009)
Standards have been established for the quality of effluent discharged from treatment plants to receiving waters. In Malaysia, there are wastewater treatment plants that are not in compliance with the enforcement by the Department of Environment (DOE). Effluents that are discharged are not complying the standard will affect receiving water and ecosystems. This study mainly focused on the performance of wastewater treatment plants in UiTM Shah Alam Campus. Three wastewater treatment plants were selected namely wastewater treatment plants at Mawar College, Teratai College and Seroja College. To achieve the objectives, the laboratory experiments were carried out to analyze the quality of the wastewater generated from the selected wastewater treatment plants. The experiments include test for chemical oxygen demand (COD) and suspended solid (SS). The result shows that only wastewater treatment plant at Seroja College that comply with Standard B. Wastewater treatment plants at Mawar College and Teratai College are not comply against standard and need to be upgraded.